"As Long as You Ask": A Qualitative Study of Biobanking Consent—Oncology Patients' and Health Care Professionals' Attitudes, Motivations, and Experiences—the B‐PPAE Study. (9th November 2018) - Yip, Sonia; Fleming, Jennifer; Shepherd, Heather L.; Walczak, Adam; Clark, Jonathan; Butow, Phyllis
Abstract: Introduction: Consent to biobanking remains controversial, with little empirical data to guide policy and practice. This study aimed to explore the attitudes, motivations, and concerns of both oncology patients and health care professionals (HCPs) regarding biobanking. Materials and Methods: Qualitative interviews were conducted with oncology patients and HCPs purposively selected from five Australian hospitals. Patients were invited to give biobanking consent as part of a clinical trial and/or for future research were eligible. HCPs were eligible if involved in consenting patients to biobanking or to donate specimens to clinical trials. Results: Twenty‐two patients participated, with head and neck (36%) and prostate (18%) the most common cancer diagnoses; all had consented to biobanking. Twenty‐two HCPs participated, from across eight cancer streams and five disciplines. Themes identified were (a) biobanking is a "no brainer"; (b) altruism or scientific enquiry; (c) trust in clinicians, science, and institutions; (d) no consent—just do it; (e) respecting patient choice ("opt‐out"); (f) respectful timing of the request; (g) need for emotional/family support; (h) context of the biobanking request matters; and (i) factors for biobanking success. Discussion: These findings reinforced previous findings regarding high public trust in, and support for, biobanking. An initial opt‐in consent approach with the option of later opt‐out was favored by patients to respect and recognize donor generosity, whereas HCPs preferred an upfront opt‐out model. Factors impacting biobanking success included the context of the request for use in a trial or specific research question, pre‐existing patient and HCP rapport, a local institution champion, and infrastructure. Abstract : This article reports on the attitudes, motivations, and concerns of oncology patients and health care professionals regarding biobanking.